Outpatients’ Perspectives on Problems and Needs Related to Female Genital Mutilation/Cutting: A Qualitative Study from Somaliland - Sarah Fried; Amina Mahmoud Warsame; Vanja Berggren; Elisabeth Isman; Annika Johansson (Obstetrics and Gynecology International)
Aim. To explore female outpatients’ perspectives on problems related to female genital mutilation/cutting (FGM/C) and their views on information, care, and counseling. Setting. An FGM/C support center at a maternity clinic in Hargeisa, Somaliland. Methods. A qualitative, descriptive study, using content analysis of seven semistructured interviews with female outpatients. Results. All participants had been ignorant of the etiology of their FGM/C-related complications and hesitant to seek care. All had undergone infibulation but did not wish the same for their daughters. In recent years they had learnt through religious leaders and media campaigns that infibulation was unapproved by Islam. A less severe FGM/C type, “Sunna,” was more accepted; however, few could define what “Sunna” meant. Condemning and ridiculing attitudes against uncircumcised women prevailed in their community. Conclusions. New ideas and concepts related to FGM/C enter the common discourse in the Somali society while traditional norms and values still prevail. Religion was shown to have a strong impact on FGM/C practices and beliefs. Interventions aiming to raise awareness of health consequences of all types of FGM/C, as well as where to seek care for complications, are needed in Somaliland. Involvement of religious leaders in anti-FGM/C programs is essential.